SLUT SHAMMING SUFFERED BY HANNAH BAKER IN JAY ASHER’S THIRTEEN REASONS WHY - IDHA NURAIDA HAVINA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Slut shaming is a common issue that becomes another form of bullying and tends to go unnoticed by the public. Partly, it is experienced by a girl or woman in high school through sexual behavior or activity. This study explores the presentation of slut shaming in the literary work, Jay Asher’s Thirteen Reasons Why. The novel is reviewed as realistic fiction that shares slut shaming issue. Two objectives are illustrated here as, to find out how is slut shaming was experienced by Hannah Baker and what are the impacts of slut shaming toward Hannah’s life in Jay Asher’s Thirteen Reasons Why. It discusses the issue of slut shaming that happened to the main character by applying the theories of Jessica Ring rose and Emma Renold. The first results of this study reveal that Hannah Baker has experience slut shaming from her close friend. As the main character, she told the whole of her story through thirteen tapes and has some people on her special list. Being labeled as a slut and bad rumors show that she gets different treatment from her friends at school. The second result is about some psychological impacts of slut shaming toward Hannah Baker’s life in the novel. Here, Hannah shows a huge impact until makes her thought of suicide. Key words : Slut shaming, The psychological impacts, High School, Thirteen Reasons Why